Evaluation of Antibacterial Activity for Non-Polar and Polar Fractions of Red Palm Fruit (Cyrtostachys renda Blume) against the Staphylococcus aureus and Escherichia coli - Putri, Fanisa Dwita; Sabrina, Nurul; Putri, Dhea Aprilia; Syamsurizal; Pratiwi, Puspa Dwi; Maimum; Utami, Diah Tri; Elisma (Journal of Herbal, Clinical and Pharmaceutical Science (HERCLIPS), 2025)
An unfavorable climate may contribute to the spread of infections. Infectious diseases can be caused by bacteria, fungi, viruses, or parasites. Phytochemical screening of fractionates ethyl acetate extract from red palm fruit (Cyrtostachys renda B.) has identified several secondary metabolites with antibacterial properties. These components include phenolics, tannins, and saponins. Secondary metabolites were fractionated using Vacuum Liquid Chromatography (VLC) and Column Chromatography (CC) techniques, resulting in both polar and non-polar fractions. The polar fraction of red palm fruit, extracted with methanol, shows antibacterial activity exclusively against gram-negative bacteria. The most significant inhibition zone is observed at a concentration of 92%. In contrast, the non-polar fraction, obtained using ethyl acetate, demonstrates antibacterial activity against both gram-positive and gram-negative bacteria. The concentration used affects the size of the inhibitory zone formed.